Simulation of instabilities in non-softening Drucker-Prager plasticity - Stankiewicz, Anna; Pamin, Jerzy (Computer Assisted Methods in Engineering and Science, 2023)
The problem of instability and strain localization in a hardening non-associative Drucker-Prager plasticity theory is analyzed. The classical and gradient-enhanced versions of the theory are reviewed and instability indicators are summarized. The regularizing properties of the gradient-enhancement are shown. The classical plane strain biaxial compression test is analyzed in terms of the analytical prediction of ellipticity loss and numerical simulation of the pr,ocess of shear band formation and evolution. The influence of material model parameters, especially of the degree of non-associativity and the gradient influence, on the instability properties is demonstrated.